Maternal monosaccharide diets evoke cognitive, locomotor, and emotional disturbances in adolescent and young adult offspring rats - Witek, Kacper; Wydra, Karolina; Suder, Agata; Filip, Małgorzata (Frontiers in Nutrition, 2023)
Anxiety and depression are the most common mental disorders affecting people worldwide. Recent studies have highlighted that a maternal high-sugar diet (HSD) could be a risk factor for neurobehavioural dysregulations, including mood disorders. Increased consumption of added sugar in food such as refined fructose/glucose can increase the risk of metabolic disorders and impact susceptibility to mental disorders. Furthermore, a few papers have reported disabilities in learning and memory among offspring after maternal HSD, thus suggesting a relationship between maternal nutrition and offspring neurogenesis. In this study, we evaluated the impact of maternal monosaccharide consumption based on a glucose (GLU) or fructose (FRU) diet during pregnancy and lactation in adolescent and young adult offspring rats of both sexes on cognitive, locomotor, and emotional disturbances. Locomotor activity, short-term memory, anxiety-like and depressive-like behavior were evaluated in the offspring. We report for the first time that the maternal GLU or FRU diet is sufficient to evoke anxiety-like behavior among adolescent and young adult offspring. Moreover, we found that maternal monosaccharide diets lead to hyperactivity and depressive-like behavior in male adolescent rats. We also noticed that a maternal FRU diet significantly enhanced novelty-seeking behavior only in young adult male rats. Our novel findings indicated that the maternal monosaccharide diet, especially a diet enriched in FRU, resulted in strong behavioral alterations in offspring rats at early life stages. This study also revealed that male rats were more susceptible to hyperactivity and anxiety- and depressive-like phenotypes than female rats. These results suggest that maternal monosaccharide consumption during pregnancy and lactation is an important factor affecting the emotional status of offspring.